Problem-Based Learning dalam Meningkatkan Higher Order Thinking Skills Mahasiswa - Edi Susanto; Agus Susanta (ARITHMETIC: Academic Journal of Math, 2022)
The research objective was to improve students' Higher Order Thinking Skills (HOTS) in basic statistics courses through the application of Problem-Based Learning (PBL). This type of research is classroom action research in two cycles with four stages: planning, implementing, observing, and reflecting. The research subjects were 34 students of mathematics education at the University of Bengkulu with 26 female and 8 male students. The research instrument was a HOTS test in the form of a description. The results showed that the application of the PBL model increased student HOTS in basic statistics courses. The increase showed the value of HOTS and classical completeness in the pre-cycle, cycle I, and cycle II. Improvement of HOTS students' abilities is carried out with an emphasis on problem-solving and evaluation as well as emphasizing relevant real problems as a starting point for concept locking.